2017
DOI: 10.1002/cpt.903
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Translational Research of ABCG2 (BCRP) in Human Disease and Drug Response

Abstract: Reverse translational research takes a bedside-to-bench approach, using sophisticated basic research to explain the biological mechanisms behind observed clinical data. For transporters, which play a role in human disease and drug response, this approach offers a distinct advantage over the typical translational research, which often falters due to inadequate in vitro and preclinical animal models. Research on ABCG2, which encodes the Breast Cancer Resistance Protein, has benefited immensely from a reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 69 publications
(79 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, besides changes in dietary intake and nutritional requirement, ontogeny of renal transporters can alter the disposition of endogenous compounds, suggesting important developmental roles for these renal transporters. Both BCRP and URAT1 are thought to play a clear role in uric acid (UA) homeostasis . It was previously reported that the fractional excretion of UA (FEUA; the % of filtered UA not reabsorbed by the tubules), was 30–40% in term newborns < 5 days old, which then decreased to 8–10% in children of 3 years old .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, besides changes in dietary intake and nutritional requirement, ontogeny of renal transporters can alter the disposition of endogenous compounds, suggesting important developmental roles for these renal transporters. Both BCRP and URAT1 are thought to play a clear role in uric acid (UA) homeostasis . It was previously reported that the fractional excretion of UA (FEUA; the % of filtered UA not reabsorbed by the tubules), was 30–40% in term newborns < 5 days old, which then decreased to 8–10% in children of 3 years old .…”
Section: Discussionmentioning
confidence: 99%
“…Both BCRP and URAT1 are thought to play a clear role in uric acid (UA) homeostasis. 23,24 It was previously reported that the fractional excretion of UA (FEUA; the % of filtered UA not reabsorbed by the tubules), was 30-40% in term newborns < 5 days old, which then decreased to 8-10% in children of 3 years old. [25][26][27] Our transporter maturation data, in addition to age-related physiological changes (e.g., urinary acidification and concentration ability), may explain this observation: the decreasing BCRP mRNA expression from birth is accompanied by an increased expression of URAT1, a reabsorptive transporter, from birth until childhood, resulting in a net decrease in UA excretion.…”
Section: Transporter-dependent Maturation Patterns During the Earliesmentioning
confidence: 99%
“…The majority of these genes function as tumor suppressors in different cancers. We found genes including HP1α, multidrug resistance gene ABCG2 [ 44 ], ANGPTL4, APC2, u-PA, JPH3, TLN1, and TERT, and signaling pathways involved in cellular differentiation, growth, adhesion, angiogenesis, hypoxia, apoptotic, canonical Wnt, and toll-like receptor signaling pathways were differentially expressed or significantly altered in lung cancer cells upon G9a knockdown. A study showed that G9a knockdown in breast cancer changed a cohort of genes involved in EMT, a phenotypic conversion linked with metastasis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although post-transcriptional and translational regulation are involved in BCRP regulation [10][11][12], it is well documented that the regulation of BCRP mainly occurs at the transcriptional level [13][14][15].…”
Section: Introductionmentioning
confidence: 99%